Organic silicon marine antifouling and anticorrosive coating with high adhesive force as well as preparation method and application of organic silicon marine antifouling and anticorrosive coating

The organosilicon marine antifouling and anticorrosion coating prepared by photo-initiated thiol-ene click reaction solves the problems of poor adhesion and mechanical stability of organosilicon coatings on substrates, and achieves high adhesion and excellent antifouling performance, making it suitable for the field of marine antifouling and anticorrosion coatings.

CN119286398AActive Publication Date: 2025-01-10TIANJIN UNIV

Patent Information

Application Number
CN202411616063.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-10
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

Existing silicone marine antifouling coatings suffer from weak adhesion to substrates and poor mechanical stability, making it difficult to simultaneously achieve excellent antifouling properties, substrate adhesion, and mechanical performance.

Method used

By using a photo-initiated thiol-ene click reaction, dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto-dimethylsiloxane, and N-(2,4,6-trichlorophenyl)maleimide were crosslinked to prepare a highly adhesive organosilicon marine antifouling and anticorrosion coating.

Benefits of technology

The prepared coating has good substrate adhesion, excellent mechanical properties and antifouling properties, meeting the needs of marine applications and effectively preventing the adhesion and corrosion of fouling organisms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286398A_ABST
    Figure CN119286398A_ABST
Patent Text Reader

Abstract

The invention discloses an organosilicone marine antifouling and anticorrosive coating with high adhesive force as well as a preparation method and application thereof. The organosilicone marine antifouling and anticorrosive coating is obtained by photocuring a composite coating material coated on the surface of a base material, the composite coating material is prepared from dopamine acrylamide, hexahedral polysilsesquioxane modified by sulfydryl, sulfydryl polydimethylsiloxane, N-(2, 4, 6-trichlorophenyl) maleimide, a photoinitiator and methylbenzene. The process provided by the invention is simple in synthesis condition, clean and environment-friendly, the ultraviolet light-initiated cross-linking reaction is rapid and good in effect, and the prepared antifouling and anticorrosive coating has good base material adhesion, excellent mechanical properties and antifouling and anticorrosive properties, and is suitable for industrial production. The requirements on antifouling property, base material adhesion and mechanical strength of the organic silicon coating in marine application can be greatly met, and the preparation method has a wide application prospect in the field of marine antifouling and anticorrosive coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of marine antifouling and anticorrosion coatings, and in particular to an organic silicon marine antifouling and anticorrosion coating with high adhesion, a preparation method thereof and uses thereof. Background Art

[0002] There are hundreds of thousands of organisms growing in the ocean, among which there is a type of marine organisms that grow fixedly on artificial facilities (such as ships, docks, buoys, etc.) called fouling organisms. Fouling organisms attached to underwater surfaces will increase fluid dynamic resistance, damage ship maneuverability, increase fuel consumption, block circulation pipes and damage equipment, resulting in huge economic maintenance costs and environmental safety issues. In addition, marine corrosion caused by marine biofouling will cause tiny cracks on the surface, which will gradually lead to large-scale corrosion, reduce surface strength, and cause serious safety problems. Therefore, it is crucial to effectively control biofouling and inhibit environmental corrosion on surfaces submerged in the ocean.

[0003] In order to eliminate the trouble caused by marine biofouling, people have adopted a series of technical means to deal with it, mainly physical methods such as mechanical cleaning, ultrasonic treatment, ultraviolet light irradiation, and chemical methods such as electrolysis of seawater and use of marine antifouling coatings. Among them, the mechanical cleaning method requires frogmen to regularly use high-pressure water guns or scrapers of underwater robots to destroy and remove biofouling attached to underwater surfaces. However, this method is time-consuming and labor-intensive, requires frequent maintenance, and causes great damage to the substrate; ultrasonic treatment kills fouling organisms by applying high-frequency sound waves (20-100Hz), but due to the need for an external ultrasonic transmitter and energy dissipation, it is only suitable for narrow spaces such as seawater pipes; ultraviolet light irradiation uses the principle that ultraviolet light can denature proteins to kill fouling organisms to achieve anti-fouling, but due to the limitations of irradiation area and distance, it is rarely used; electrolysis of seawater is to electrolyze chlorides in seawater, and the sodium hypochlorite produced can destroy the cell tissues of fouling organisms and make them lose their adhesion ability, but because the ocean is an open system, the sodium hypochlorite generated by electrolysis will be infinitely diluted by seawater, causing the concentration to drop rapidly to below the effective concentration, so this method is also only suitable for closed and narrow spaces. Compared with physical anti-fouling technology, chemical anti-fouling technology has the advantages of long anti-fouling time, significant anti-fouling effect, and simple and easy anti-fouling technology, so it has a wider range of applications. Applying marine anti-fouling coatings is currently the most effective, economical, simplest and most widely used method.

[0004] Silicone marine antifouling coatings belong to the field of environmentally friendly fouling-releasing antifouling coatings. Based on low surface free energy and low elastic modulus, they can achieve the prevention and control of fouling organisms and the removal of loosely adhered fouling organisms by taking advantage of the relative movement between the ship and the seawater, and have great application prospects. However, due to the low modulus of PDMS (~1 MPa), it is easily mechanically damaged in practical applications. In addition, due to its non-polarity and inertness, PDMS has weak adhesion to the substrate. Modification of linear PDMS elastomers with different groups (epoxy resin, catechol, polyurethane, urea, 2uredo-4[1H]-pyrimidine, etc.) can improve its substrate adhesion and mechanical properties, but due to the surface changes caused by these polar groups, its antifouling ability is usually sacrificed. Adding inorganic particles (SiO2, nanodiamonds, graphene oxide, multi-walled carbon nanotubes, etc.) to improve substrate adhesion often increases surface roughness, thereby weakening the antifouling performance. Therefore, achieving excellent antifouling, substrate adhesion and mechanical properties simultaneously is a major challenge facing silicone antifouling and anticorrosion coatings. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a highly adhesive organosilicon marine antifouling and anticorrosion coating, a preparation method and uses thereof, which overcome the defects of the prior art organosilicon coatings in terms of weak adhesion to the substrate and poor mechanical stability.

[0006] The technical solution adopted to achieve the purpose of the present invention is:

[0007] In a first aspect, the present invention provides an organosilicon marine antifouling and anticorrosion coating with high adhesion, wherein the organosilicon marine antifouling and anticorrosion coating is obtained by photocuring a composite coating material coated on a substrate surface;

[0008] The composite coating material comprises dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide, a photoinitiator and toluene.

[0009] Organosilicon marine antifouling coatings belong to the field of environmentally friendly fouling-releasing antifouling coatings. Based on low surface free energy and low elastic modulus, they can achieve the prevention and control of fouling organisms and the removal of loosely adhered fouling organisms by means of the relative movement between the ship and the seawater, and have great application prospects. The present invention cross-links dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane and N-(2,4,6-trichlorophenyl) maleimide through a photo-triggered thiol-ene click reaction to prepare an organosilicon marine antifouling and anticorrosion coating with high adhesion.

[0010] Dopamine is the main component of adhesive proteins in many marine organisms. Due to the chemical versatility and affinity diversity of the catechol functional groups in its structure, dopamine has unique chemical properties. The catechol structure provides a strong anchoring effect. Dopamine acrylamide acts as a biomimetic anchor to ensure a strong bond between the coating and the substrate, so that the antifouling and anticorrosion coating is firmly attached to the substrate. As a new type of organic / inorganic hybrid nanomaterial, the special structure of thiol-modified hexahedral polysilsesquioxane, which combines the internal inorganic rigid structure and the external organic group, can effectively improve the compatibility with the organic substrate. Due to the advantages of the Si-O-Si inorganic core structure, the antifouling and anticorrosion coating has good mechanical stability. The hydrophobicity of polydimethylsiloxane and the bactericidal property of N-(2,4,6-trichlorophenyl) maleimide provide excellent antifouling properties for the antifouling and anticorrosion coating.

[0011] The process provided by the invention has simple synthesis conditions, is clean and environmentally friendly, the ultraviolet light-induced cross-linking reaction is rapid and has good effect, and the prepared antifouling and anticorrosion coating has good substrate adhesion, excellent mechanical properties and antifouling and anticorrosion properties, and can greatly meet the requirements for antifouling properties, substrate adhesion and mechanical strength of silicone coatings in marine applications, and has broad application prospects in the field of marine antifouling and anticorrosion coatings.

[0012] As a preferred technical solution of the present invention, the mass ratio of the dopamine acrylamide, the thiol-modified hexahedral polysilsesquioxane, the thiol polydimethylsiloxane, the N-(2,4,6-trichlorophenyl)maleimide and the photoinitiator is (0.5-5):(0.5-5):(10-50):(0.5-2):(1-10), for example, it can be 0.5:0.5:10:0.5:1, 1:1:15: 0.6:2, 1.5:1.5:20:0.7:3, 2:2:25:0.8:4, 2.5:2.5:30:1:5, 3:3:35:1.2:6, 3.5:3.5:40:1.5:7, 4:4:45:1.6:8, 4.5:4.5:50:1.8:9 or 5:5:50:2:10, but are not limited to the listed values, other values ​​not listed within the numerical range are also applicable.

[0013] In some optional examples, the total mass ratio of the dopamine acrylamide, the thiol-modified hexahedral polysilsesquioxane, the thiol polydimethylsiloxane, the N-(2,4,6-trichlorophenyl)maleimide and the photoinitiator to the volume of the toluene is (0.0625-0.375) g:1 mL, for example, 0.0625 g:1 mL, 0.08 g:1 mL, 0.1 g:1 mL, 0.12 g:1 mL, 0.18 g:1 mL, 0.20 g:1 mL, 0.36 g:1 mL, 0.40 g:1 mL, 0.50 g:1 mL, 0.60 g:1 mL, 0.70 g:1 mL, 0.80 g:1 mL, 0.90 g:1 mL, 0.15 g:1 mL, 0.20 g:1 mL, 0.36 g:1 mL, 0.40 g:1 mL, 0.50 g:1 mL, 0.60 g:1 mL, 0.70 g:1 mL, 0.80 g:1 mL, 0.90 g:1 mL, 0. .14g:1mL, 0.16g:1mL, 0.18g:1mL, 0.2g:1mL, 0.22g:1mL, 0.24g:1mL, 0.26g:1mL, 0.28g:1mL, 0.3g:1mL, 0.32g:1mL, 0.34g:1mL, 0.36g:1mL or 0.375g:1mL, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] As a preferred technical solution of the present invention, the photoinitiator includes benzoin ethers and / or benzophenones, preferably benzoin dimethyl ether.

[0015] In some optional examples, the material of the substrate includes any one of iron, aluminum, copper or glass.

[0016] In a second aspect, the present invention provides a method for preparing the organic silicon marine antifouling and anticorrosion coating according to the first aspect, the preparation method comprising:

[0017] Dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane, N-(2,4,6-trichlorophenyl)maleimide and a photoinitiator are dissolved in toluene, mixed evenly to obtain a composite coating material, the composite coating material is evenly coated on the surface of a substrate, and the organic silicon marine antifouling and anticorrosion coating is obtained by ultraviolet curing.

[0018] As a preferred technical solution of the present invention, the dopamine acrylamide is prepared by the following method:

[0019] Dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution, methyl acrylic anhydride solution is added dropwise to the precursor solution, and a reaction solution is obtained after uniform mixing. Alkaline solution is added dropwise to the reaction solution to adjust the pH value thereof, the reaction solution is heated to cause a nucleophilic reaction, and after the reaction is completed, separation and purification are performed to obtain the dopamine acrylamide.

[0020] As a preferred technical solution of the present invention, the mass ratio of the dopamine hydrochloride, the sodium borate, the sodium carbonate, the deionized water and the methacrylic anhydride solution is (1-10):(5-20):(1-10):(100-150):(1-10), for example, it can be 1:5:1:100:1, 2:6:2:105:2, 3:7:3:110:3, 4:8:4:115:4, 5:9:5:120:5, 6:10:6:125:6, 7:12:7:130:7, 8:13:8:135:8, 9:14:9:140:9 or 10:15:10:150:10, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In some optional examples, the methacrylic anhydride solution consists of methacrylic anhydride and an organic solvent, wherein the organic solvent includes any one of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone, or a combination of at least two thereof.

[0022] In some optional examples, the mass fraction of the methacrylic anhydride solution is 90-95wt%, for example, it can be 90wt%, 90.5wt%, 91wt%, 91.5wt%, 92wt%, 92.5wt%, 93wt%, 93.5wt%, 94wt%, 94.5wt% or 95wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional examples, the concentration of the alkali solution is 0.1-3.0 mol / L, for example, it can be 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.4 mol / L, 2.6 mol / L, 2.8 mol / L or 3.0 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional examples, alkaline solution is added dropwise to the reaction solution to adjust its pH value to 8-10, for example, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In some optional examples, the heating temperature of the nucleophilic reaction of the reaction solution is 25-65°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, and it is further preferably 28-40°C.

[0026] In some optional examples, the heating time of the nucleophilic reaction of the reaction solution is 6 to 36 h, for example, it can be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 26 h, 28 h, 30 h, 32 h, 34 h or 36 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional examples, the separation and purification process includes:

[0028] Acid solution is added dropwise to the reaction product obtained by the nucleophilic reaction to adjust the pH value thereof to 1-2, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0; then ethyl acetate and / or n-hexane are used as extractants for extraction, preferably a mixture of n-hexane and ethyl acetate in a volume ratio of (0.25-0.65):1 is used as the extractant, for example, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1 or 0.65:1, but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0029] As a preferred technical solution of the present invention, the thiol-modified hexahedral polysilsesquioxane is prepared by the following method:

[0030] (3-mercaptopropyl)trimethoxysilane and hydrochloric acid solution are added to methanol for condensation reaction. After the reaction is completed, the hexahedral polysilsesquioxane modified with mercapto group is obtained by separation and purification.

[0031] As a preferred technical solution of the present invention, the mass fraction of the hydrochloric acid solution is 35-40wt%, for example, it can be 35wt%, 35.5wt%, 36wt%, 36.5wt%, 37wt%, 37.5wt%, 38wt%, 38.5wt%, 39wt%, 39.5wt% or 40wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the volume ratio of the (3-mercaptopropyl)trimethoxysilane, the hydrochloric acid solution and the methanol is (1-5):(1-10):(30-80), for example, it can be 1:1:30, 1.5:2:35, 2:3:40, 2.5:4:45, 3:5:50, 3.5:6:60, 4:7:65, 4.5:8:70, 5:9:75 or 5:10:80, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the temperature of the condensation reaction is 70-120°C, for example, it can be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the condensation reaction time is 18 to 30 hours, for example, it can be 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours, 28 hours, 29 hours or 30 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] As a preferred technical solution of the present invention, the wavelength of ultraviolet light used in the ultraviolet light curing is 365nm.

[0036] In some optional examples, the power of the ultraviolet light source used for the ultraviolet light curing is 1 to 5 W, for example, it can be 1.0 W, 1.5 W, 2.0 W, 2.5 W, 3.0 W, 3.5 W, 4.0 W, 4.5 W or 5.0 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional embodiments, the UV light intensity used in the UV curing is 0.48-2.0 W / cm 2 , for example, it can be 0.48W / cm 2 , 0.5W / cm 2 , 1.0W / cm 2 , 1.1W / cm 2 , 1.2W / cm 2 , 1.3W / cm 2 , 1.4W / cm 2 , 1.5W / cm 2 , 1.6W / cm 2 , 1.7W / cm 2 、1.8W / cm 2 、1.9W / cm 2or 2.0W / cm 2 , but is not limited to the listed values, other values ​​not listed in the numerical range are also applicable, preferably 0.8 to 1.6 W / cm 2 .

[0038] In some optional examples, the UV curing time is 60 to 300 s, for example, 60 s, 70 s, 80 s, 90 s, 100 s, 150 s, 200 s, 250 s or 300 s, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 80 to 300 s.

[0039] In a third aspect, the present invention provides a use of the organic silicon marine antifouling and anticorrosion coating with high adhesion as described in the first aspect, wherein the organic silicon marine antifouling and anticorrosion coating is used for antifouling and anticorrosion of ship hulls.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] Organosilicon marine antifouling coatings belong to the field of environmentally friendly fouling-releasing antifouling coatings. Based on low surface free energy and low elastic modulus, they can achieve the prevention and control of fouling organisms and the removal of loosely adhered fouling organisms by means of the relative movement between the ship and the seawater, and have great application prospects. The present invention cross-links dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane and N-(2,4,6-trichlorophenyl) maleimide through a photo-triggered thiol-ene click reaction to prepare an organosilicon marine antifouling and anticorrosion coating with high adhesion.

[0042] Dopamine is the main component of adhesive proteins in many marine organisms. Due to the chemical versatility and affinity diversity of the catechol functional groups in its structure, dopamine has unique chemical properties. The catechol structure provides a strong anchoring effect. Dopamine acrylamide acts as a biomimetic anchor to ensure a strong bond between the coating and the substrate, so that the antifouling and anticorrosion coating is firmly attached to the substrate. As a new type of organic / inorganic hybrid nanomaterial, the special structure of thiol-modified hexahedral polysilsesquioxane, which combines the internal inorganic rigid structure and the external organic group, can effectively improve the compatibility with the organic substrate. Due to the advantages of the Si-O-Si inorganic core structure, the antifouling and anticorrosion coating has good mechanical stability. The hydrophobicity of polydimethylsiloxane and the bactericidal property of N-(2,4,6-trichlorophenyl) maleimide provide excellent antifouling properties for the antifouling and anticorrosion coating.

[0043] The process provided by the invention has simple synthesis conditions, is clean and environmentally friendly, the ultraviolet light-induced cross-linking reaction is rapid and has good effect, and the prepared antifouling and anticorrosion coating has good substrate adhesion, excellent mechanical properties and antifouling and anticorrosion properties, and can greatly meet the requirements for antifouling properties, substrate adhesion and mechanical strength of silicone coatings in marine applications, and has broad application prospects in the field of marine antifouling and anticorrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A process flow chart of the preparation of the organosilicon marine antifouling and anticorrosive coating provided in Examples 1-9 of the present invention;

[0045] Figure 2 This is the infrared spectrum of the dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane and organosilicon marine antifouling and anticorrosion coating prepared in Example 1 of the present invention:

[0046] Figure 3 This is a surface scanning electron microscope image of the organosilicon marine antifouling and anticorrosion coating prepared in Example 1 of the present invention;

[0047] Figure 4 This is a cross-sectional scanning electron microscope image of the organic silicon marine antifouling and anticorrosion coating prepared in Example 1 of the present invention;

[0048] Figure 5 This is a real sea hanging board test picture of the organosilicon marine antifouling and anticorrosion coating prepared in Example 1 of the present invention;

[0049] Figure 6 This is a real sea hanging board test picture of the organosilicon marine antifouling and anticorrosion coating prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0050] In order to fully and clearly describe the technical solution of the present invention, the present invention will be further explained below in conjunction with the accompanying drawings and embodiments of the specification. The embodiments described are only part of the embodiments of the present invention, and the implementation methods of the present invention are not limited thereto.

[0051] Example 1

[0052] This embodiment provides a method for preparing an organosilicon marine antifouling and anticorrosion coating with high adhesion, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0053] (1) Preparation of dopamine acrylamide: dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution; a 90 wt% methacrylic anhydride solution is added dropwise to the precursor solution, and the mixture is mixed uniformly to obtain a reaction solution, wherein the mass ratio of dopamine hydrochloride, sodium borate, sodium carbonate, deionized water and methacrylic anhydride solution is 1:5:1:100:1; a 0.1 mol / L sodium hydroxide solution is added dropwise to the reaction solution to adjust its pH value to 8, and then the reaction solution is heated to 25° C. and mixed and stirred for 36 hours to cause a nucleophilic reaction;

[0054] After the reaction is completed, the reaction product is washed twice with 50 mL of ethyl acetate, the solid in the solution is vacuum filtered, the obtained solution is acidified to a pH value of 1 with a 6M hydrochloric acid solution, and the organic layer is extracted from the acidified aqueous solution with 50 mL of ethyl acetate three times; the transparent brown organic layer extracted in ethyl acetate is dried with MgSO4, the volume of the solution is reduced to 25 mL with a rotary evaporator, the obtained solution is added to 250 mL of n-hexane, and vigorously stirred to precipitate a brown solid, the formed suspension is refrigerated to maximize the size of the crystals formed, the obtained light brown solid is dissolved in 20 mL of ethyl acetate, and then precipitated and purified in 300 mL of n-hexane, and the obtained solid powder is dried overnight in a vacuum to obtain dopamine acrylamide;

[0055] (2) Preparation of thiol-modified hexahedral polysilsesquioxane: (3-mercaptopropyl)trimethoxysilane and a 35 wt% hydrochloric acid solution are added to methanol for condensation reaction, wherein the volume ratio of (3-mercaptopropyl)trimethoxysilane, hydrochloric acid solution and methanol is 1:1:30, the condensation reaction temperature is 70°C, the condensation reaction time is 30 hours, and after the reaction is completed, the thiol-modified hexahedral polysilsesquioxane is obtained by separation and purification;

[0056] (3) Preparation of organic silicon marine antifouling and anticorrosion coating: dissolving the dopamine acrylamide obtained in step (1), the thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether obtained in step (2) in toluene, wherein the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether is 0.5:0.5:10:0.5:1, and the total mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether to the volume of toluene is 0.0625 g:1 mL, and mixing them evenly to obtain a composite coating material;

[0057] The composite coating material was evenly coated on the surface of the stainless steel plate and irradiated with ultraviolet light of 365nm wavelength, wherein the power of the ultraviolet light source was 1W and the ultraviolet light intensity was 0.48W / cm 2 The irradiation time is 300s, and the organic silicon marine antifouling and anticorrosion coating is obtained after curing.

[0058] The infrared spectra of the dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane and organosilicon marine antifouling and anticorrosion coating prepared in this example are shown in FIG. Figure 2 As shown in the figure, the characteristic peaks of each group in the coating and raw materials are clearly visible, 2557cm -1 The characteristic peak is the stretching vibration peak of -SH, 1259cm -1 The characteristic peak at 1112cm is the symmetrical deformation vibration absorption peak of Si-(CH3)2. -1 The sharp peak at 690 cm-1 should be the characteristic absorption peak of the Si-O-Si skeleton in the cage-type silsesquioxane, proving the formation of the POSS cage. -1 The characteristic peak at 3189cm is the out-of-plane bending vibration peak of Si-(CH3)2. -1 The stretching vibration peak of -OH is 1653cm -1 The absorption peak of -NC=O is 1594cm -1 The absorption peak of C=C is 1396cm -1 and 1191cm -1 The absorption peak of benzene ring is at 2557cm -1 The stretching vibration peaks of -SH at 1594 cm -1 The C=C absorption peak at 47° disappeared, indicating that a thiol-ene click reaction occurred between -SH and C=C under the initiation of ultraviolet light.

[0059] The surface scanning electron microscope image of the organosilicon marine antifouling and anticorrosion coating prepared in this example is as follows: Figure 3 As shown in the figure, it can be seen that there are 0.1 to 0.8 μm particle protrusions distributed on the coating surface.

[0060] The cross-sectional scanning electron microscope image of the organic silicon marine antifouling and anticorrosion coating prepared in this embodiment is as follows: Figure 4 As shown in the figure, the average thickness of the coating can be measured to be 61.57 μm.

[0061] Example 2

[0062] This embodiment provides a method for preparing an organosilicon marine antifouling and anticorrosion coating with high adhesion, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0063] (1) Preparation of dopamine acrylamide: dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution; a 91 wt% methacrylic anhydride solution is added dropwise to the precursor solution, and the mixture is mixed uniformly to obtain a reaction solution, wherein the mass ratio of dopamine hydrochloride, sodium borate, sodium carbonate, deionized water and methacrylic anhydride solution is 3:10:3:110:3; a 0.5 mol / L sodium hydroxide solution is added dropwise to the reaction solution to adjust its pH value to 8.5, and then the reaction solution is heated to 35° C. and mixed and stirred for 30 h to cause a nucleophilic reaction;

[0064] After the reaction is completed, the reaction product is washed twice with 50 mL of ethyl acetate, the solid in the solution is vacuum filtered, the obtained solution is acidified to a pH value of 1 with a 6M hydrochloric acid solution, and the organic layer is extracted from the acidified aqueous solution with 50 mL of ethyl acetate three times; the transparent brown organic layer extracted in ethyl acetate is dried with MgSO4, the volume of the solution is reduced to 25 mL with a rotary evaporator, the obtained solution is added to 250 mL of n-hexane, and vigorously stirred to precipitate a brown solid, the formed suspension is refrigerated to maximize the size of the crystals formed, the obtained light brown solid is dissolved in 20 mL of ethyl acetate, and then precipitated and purified in 300 mL of n-hexane, and the obtained solid powder is dried overnight in a vacuum to obtain dopamine acrylamide;

[0065] (2) Preparation of thiol-modified hexahedral polysilsesquioxane: (3-mercaptopropyl)trimethoxysilane and a 36 wt % hydrochloric acid solution were added to methanol for condensation reaction, wherein the volume ratio of (3-mercaptopropyl)trimethoxysilane, hydrochloric acid solution and methanol was 2:3:40, the condensation reaction temperature was 80° C., the condensation reaction time was 27 h, and after the reaction was completed, the thiol-modified hexahedral polysilsesquioxane was obtained by separation and purification;

[0066] (3) Preparation of organic silicon marine antifouling and anticorrosion coating: dissolving the dopamine acrylamide obtained in step (1), the thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether obtained in step (2) in toluene, wherein the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether is 1:1:20:0.8:3, and the total mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether to the volume of toluene is 0.1 g:1 mL, and mixing them evenly to obtain a composite coating material;

[0067] The composite coating material was evenly coated on the surface of the stainless steel plate and irradiated with ultraviolet light of 365nm wavelength, where the power of the ultraviolet light source was 2W and the ultraviolet light intensity was 1W / cm 2 The irradiation time is 240s, and the organic silicon marine antifouling and anticorrosion coating is obtained after curing.

[0068] Example 3

[0069] This embodiment provides a method for preparing an organosilicon marine antifouling and anticorrosion coating with high adhesion, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0070] (1) Preparation of dopamine acrylamide: dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution; a 92 wt% methacrylic anhydride solution is added dropwise to the precursor solution, and the mixture is mixed uniformly to obtain a reaction solution, wherein the mass ratio of dopamine hydrochloride, sodium borate, sodium carbonate, deionized water and methacrylic anhydride solution is 5:15:5:120:5; a 1 mol / L sodium hydroxide solution is added dropwise to the reaction solution to adjust its pH value to 9, and then the reaction solution is heated to 45° C. and mixed and stirred for 22 h to cause a nucleophilic reaction;

[0071] After the reaction is completed, the reaction product is washed twice with 50 mL of ethyl acetate, the solid in the solution is vacuum filtered, the obtained solution is acidified to a pH value of 1 with a 6M hydrochloric acid solution, and the organic layer is extracted from the acidified aqueous solution with 50 mL of ethyl acetate three times; the transparent brown organic layer extracted in ethyl acetate is dried with MgSO4, the volume of the solution is reduced to 25 mL with a rotary evaporator, the obtained solution is added to 250 mL of n-hexane, and vigorously stirred to precipitate a brown solid, the formed suspension is refrigerated to maximize the size of the crystals formed, the obtained light brown solid is dissolved in 20 mL of ethyl acetate, and then precipitated and purified in 300 mL of n-hexane, and the obtained solid powder is dried overnight in a vacuum to obtain dopamine acrylamide;

[0072] (2) Preparation of thiol-modified hexahedral polysilsesquioxane: (3-mercaptopropyl)trimethoxysilane and a 37 wt % hydrochloric acid solution are added to methanol for condensation reaction, wherein the volume ratio of (3-mercaptopropyl)trimethoxysilane, hydrochloric acid solution and methanol is 3:5:50, the condensation reaction temperature is 90° C., the condensation reaction time is 24 h, and after the reaction is completed, the thiol-modified hexahedral polysilsesquioxane is obtained by separation and purification;

[0073] (3) Preparation of organic silicon marine antifouling and anticorrosion coating: dissolving the dopamine acrylamide obtained in step (1), the thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether obtained in step (2) in toluene, wherein the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether is 2:2:30:1:5, and the total mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether to the volume ratio of toluene is 0.2 g:1 mL, and mixing them evenly to obtain a composite coating material;

[0074] The composite coating material was evenly coated on the surface of the aluminum plate and irradiated with ultraviolet light of 365nm wavelength, where the power of the ultraviolet light source was 3W and the ultraviolet light intensity was 1.5W / cm 2 The irradiation time is 180s, and the organic silicon marine antifouling and anticorrosion coating is obtained after curing.

[0075] Example 4

[0076] This embodiment provides a method for preparing an organosilicon marine antifouling and anticorrosion coating with high adhesion, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0077] (1) Preparation of dopamine acrylamide: dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution; a 93wt% methacrylic anhydride solution is added dropwise to the precursor solution, and the mixture is mixed uniformly to obtain a reaction solution, wherein the mass ratio of dopamine hydrochloride, sodium borate, sodium carbonate, deionized water and methacrylic anhydride solution is 8:18:8:130:8; a 2mol / L sodium hydroxide solution is added dropwise to the reaction solution to adjust its pH value to 9.5, and then the reaction solution is heated to 55°C and mixed and stirred for 14h to cause a nucleophilic reaction;

[0078] After the reaction is completed, the reaction product is washed twice with 50 mL of ethyl acetate, the solid in the solution is vacuum filtered, the obtained solution is acidified to a pH value of 1 with a 6M hydrochloric acid solution, and the organic layer is extracted from the acidified aqueous solution with 50 mL of ethyl acetate three times; the transparent brown organic layer extracted in ethyl acetate is dried with MgSO4, the volume of the solution is reduced to 25 mL with a rotary evaporator, the obtained solution is added to 250 mL of n-hexane, and vigorously stirred to precipitate a brown solid, the formed suspension is refrigerated to maximize the size of the crystals formed, the obtained light brown solid is dissolved in 20 mL of ethyl acetate, and then precipitated and purified in 300 mL of n-hexane, and the obtained solid powder is dried overnight in a vacuum to obtain dopamine acrylamide;

[0079] (2) Preparation of thiol-modified hexahedral polysilsesquioxane: (3-mercaptopropyl)trimethoxysilane and a 38 wt % hydrochloric acid solution were added to methanol for condensation reaction, wherein the volume ratio of (3-mercaptopropyl)trimethoxysilane, hydrochloric acid solution and methanol was 4:8:60, the condensation reaction temperature was 100° C., the condensation reaction time was 21 h, and after the reaction was completed, the thiol-modified hexahedral polysilsesquioxane was obtained by separation and purification;

[0080] (3) Preparation of organic silicon marine antifouling and anticorrosion coating: dissolving the dopamine acrylamide obtained in step (1), the thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether obtained in step (2) in toluene, wherein the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether is 3:3:40:1.5:8, and the total mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether to the volume ratio of toluene is 0.3 g:1 mL, and mixing them evenly to obtain a composite coating material;

[0081] The composite coating material was evenly coated on the surface of the copper plate and irradiated with ultraviolet light of 365nm wavelength, where the power of the ultraviolet light source was 4W and the ultraviolet light intensity was 1.8W / cm 2 The irradiation time is 120s, and the organic silicon marine antifouling and anticorrosion coating is obtained after curing.

[0082] Example 5

[0083] This embodiment provides a method for preparing an organosilicon marine antifouling and anticorrosion coating with high adhesion, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0084] (1) Preparation of dopamine acrylamide: dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution; a 95 wt% methacrylic anhydride solution is added dropwise to the precursor solution, and the mixture is mixed uniformly to obtain a reaction solution, wherein the mass ratio of dopamine hydrochloride, sodium borate, sodium carbonate, deionized water and methacrylic anhydride solution is 10:20:10:150:10; a 3.0 mol / L sodium hydroxide solution is added dropwise to the reaction solution to adjust its pH value to 10, and then the reaction solution is heated to 65° C. and mixed and stirred for 6 hours to cause a nucleophilic reaction;

[0085] After the reaction is completed, the reaction product is washed twice with 50 mL of ethyl acetate, the solid in the solution is vacuum filtered, the obtained solution is acidified to a pH value of 1 with a 6M hydrochloric acid solution, and the organic layer is extracted from the acidified aqueous solution with 50 mL of ethyl acetate three times; the transparent brown organic layer extracted in ethyl acetate is dried with MgSO4, the volume of the solution is reduced to 25 mL with a rotary evaporator, the obtained solution is added to 250 mL of n-hexane, and vigorously stirred to precipitate a brown solid, the formed suspension is refrigerated to maximize the size of the crystals formed, the obtained light brown solid is dissolved in 20 mL of ethyl acetate, and then precipitated and purified in 300 mL of n-hexane, and the obtained solid powder is dried overnight in a vacuum to obtain dopamine acrylamide;

[0086] (2) Preparation of thiol-modified hexahedral polysilsesquioxane: (3-mercaptopropyl)trimethoxysilane and a 40 wt% hydrochloric acid solution are added to methanol for condensation reaction, wherein the volume ratio of (3-mercaptopropyl)trimethoxysilane, hydrochloric acid solution and methanol is 5:10:80, the condensation reaction temperature is 120° C., the condensation reaction time is 18 h, and after the reaction is completed, the thiol-modified hexahedral polysilsesquioxane is obtained by separation and purification;

[0087] (3) Preparation of organic silicon marine antifouling and anticorrosion coating: dissolving the dopamine acrylamide obtained in step (1), the thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether obtained in step (2) in toluene, wherein the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether is 5:5:50:2:10, and the total mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide and benzoin dimethyl ether to the volume of toluene is 0.375 g:1 mL, and mixing them evenly to obtain a composite coating material;

[0088] The composite coating material was evenly coated on the surface of the glass plate and irradiated with ultraviolet light of 365nm wavelength, wherein the power of the ultraviolet light source was 5W and the ultraviolet light intensity was 2.0W / cm 2 The irradiation time is 60s, and the organic silicon marine antifouling and anticorrosion coating is obtained after curing.

[0089] Example 6

[0090] The present embodiment provides a method for preparing a silicone marine antifouling and anticorrosion coating with high adhesion. The difference from Example 1 is that in step (3), the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl)maleimide and photoinitiator is adjusted to 0.2:0.5:10:0.5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0091] Example 7

[0092] The present embodiment provides a method for preparing a silicone marine antifouling and anticorrosion coating with high adhesion. The difference from Example 1 is that in step (3), the mass ratio of dopamine acrylamide, thiol-modified hexahedral polysilsesquioxane, thiol polydimethylsiloxane, N-(2,4,6-trichlorophenyl)maleimide and photoinitiator is adjusted to 8:0.5:10:0.5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0093] Example 8

[0094] This embodiment provides a method for preparing a highly adhesive organosilicon marine antifouling and anticorrosion coating. The difference from Embodiment 1 is that in step (3), the curing time is adjusted to 50 seconds, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0095] Example 9

[0096] This embodiment provides a method for preparing a highly adhesive organosilicon marine antifouling and anticorrosion coating. The difference from Embodiment 1 is that in step (3), the curing time is adjusted to 350 s, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0097] Comparative Example 1

[0098] This comparative example provides a method for preparing a highly adherent organosilicon marine antifouling and anticorrosion coating. The difference from Example 1 is that step (2) is omitted, and no mercapto-modified hexahedral polysilsesquioxane is added to the composite coating material in step (3). Other process parameters and operating steps are exactly the same as those in Example 1.

[0099] Comparative Example 2

[0100] This comparative example provides a method for preparing a highly adherent organosilicon marine antifouling and anticorrosion coating. The difference from Example 1 is that N-(2,4,6-trichlorophenyl)maleimide is not added to the composite coating material in step (3), and the other process parameters and operating steps are exactly the same as those in Example 1.

[0101] Comparative Example 3

[0102] This comparative example provides a method for preparing a highly adherent organosilicon marine antifouling and anticorrosion coating. The difference from Example 1 is that step (2) is omitted, and no thiol-modified hexahedral polysilsesquioxane and N-(2,4,6-trichlorophenyl)maleimide are added to the composite coating material in step (3). Other process parameters and operating steps are exactly the same as those in Example 1.

[0103] The water contact angle, adhesion, antifouling performance and anticorrosion performance of the organic silicon marine antifouling and anticorrosion coatings prepared in each embodiment and comparative example were measured, and the test method was as follows:

[0104] (1) Water contact angle

[0105] The water contact angle was measured by a contact angle meter (Bioline Technology Co., Ltd., Sweden, model: ThetaLite), with a water drop volume of 4 μL, and the measurement was performed 5 to 15 seconds after the drop. Five points were randomly selected from each coating surface for testing, and the average of the five measurements was taken as the water contact angle value of the coating.

[0106] (2) Adhesion test

[0107] The DeFelsko PosiTest AT-A fully automatic digital display adhesion tensile tester was used to test the adhesion strength of the coating on the substrate material. According to the ASTM D4541 standard, a cylindrical aluminum ingot with a diameter of 2 cm was bonded to the coating surface with an epoxy adhesive and cured at room temperature for 3 days. After that, the coating was pulled away from the substrate at a stress loading speed of 0.2 MPa / s, and the average value of 5 different areas was taken as the measurement result.

[0108] (3) Antibacterial test

[0109] Since E. coli is commonly found in the marine environment and in daily life, the antibacterial properties of the coatings were evaluated by E. coli. Each coating was immersed in 10 ml of bacterial suspension (approximately 10 6 CFU) in a sterile culture dish and cultured at 37°C for 12 hours. After culture, rinse the coating three times with PBS buffer to remove unstable adhering bacteria and discard the rinsing solution. Subsequently, rinse the coating repeatedly to completely separate the attached bacteria and retain the rinsing solution. Spread 200 μL of the rinsing solution evenly on the LB agar culture plate and finally culture it at 37°C for another 18 hours. The antibacterial experiment was repeated three times and the average value was taken. The antibacterial rate was calculated based on the number of colonies on the plate. The antibacterial rate (R b ) is calculated as follows:

[0110]

[0111] Among them, N b and N c Refers to the number of colonies on the plates corresponding to the blank group without coating and the experimental group with coating, respectively.

[0112] (4) Anti-algae test

[0113] Nitzschiaclosterium was used to evaluate the anti-diatom adhesion performance of the coating. Nitzschiaclosterium was cultured in F / 2 medium at 25°C with a 12:12 hour light-dark cycle. The glass slide coated with the coating to be tested was placed vertically in the algae solution, so as to minimize the occurrence of diatoms depositing on the coating surface due to gravity, thereby reducing the experimental error. Three parallel experiments were performed for each group of coating samples. After the coating was soaked in the algae solution for one week, it was taken out and the diatoms that were not firmly adhered to the coating surface were gently rinsed with seawater. Then the coating was immersed in an 80wt% acetone aqueous solution to extract diatom chlorophyll. Finally, the fluorescence intensity was measured with an AMIscience chlorophyll fluorescence meter, and the anti-algae rate of the sample to be tested was calculated.

[0114] I=(1-X / Y)×100%

[0115] Wherein, I is the diatom inhibition rate; X is the fluorescence intensity of diatoms attached to the test sample; and Y is the fluorescence intensity of diatoms attached to the control sample.

[0116] (5) Actual sea hanging board test

[0117] A 90-day marine field test was conducted from September to December in the Bohai Sea, Tianjin, China (117°46′E, 39°43′N). The coating panels were mounted on stainless steel frames and immersed at a depth of 0.5m below sea level. Three replicates were used for each coating. After a period of time, the frames were removed and rinsed with natural seawater to remove unstable attached silt and biofouling. The antifouling performance of the coating was evaluated according to the national standard GB / T5370-2007 Shallow Sea Immersion Test Method for Antifouling Paint Samples, and the performance score was obtained.

[0118] The actual sea hanging board test pictures of the organosilicon marine antifouling and anticorrosion coatings prepared in Example 1 and Comparative Example 3 are shown as follows: Figure 5 and Figure 6 As shown in the figure, it can be seen that the organic silicon marine antifouling and anticorrosion coating prepared in Comparative Example 3 (such as Figure 6 The surface of the organic silicon marine antifouling and anticorrosive coating (as shown in the figure) was obviously attached with some tubeworm larvae, diatoms, barnacle larvae and other marine fouling organisms, and even a large number of large biofouling organisms, such as barnacles and mussels. Under the same test time, the organic silicon marine antifouling and anticorrosive coating (as shown in the figure) prepared in Example 1 Figure 5 Only a few diatoms were attached to the surface, and no large, intact organisms were found.

[0119] (6) Corrosion resistance test

[0120] Electrochemical measurements (Tafel polarization curves) were performed in 3.5% NaCl solution at ambient temperature using an electrochemical workstation (CHI660C, CHInstruments, USA). The experiments were performed using a typical three-electrode system, with a metal sheet (exposed area of ​​1 cm) as the working electrode. 2 ), the reference electrode is saturated calomel electrode (SCE, vs. Ag / AgCl), and the counter electrode is platinum. All measurements were performed when the open circuit potential (OCP) was stable. The Tafel plot is based on 1mVs -1 The corrosion potential (E corr ) and corrosion current (I corr ).

[0121] The above test results are shown in Table 1.

[0122] Table 1

[0123]

[0124] It can be seen from the test data provided in Table 1 that the organosilicon marine antifouling and anticorrosion coatings prepared in Examples 1-5 of the present invention have high adhesion and antifouling and anticorrosion properties.

[0125] It can be seen from the test data of Example 1, Example 6 and Example 7 that when the addition amount of dopamine acrylamide is too high or too low, the adhesion and antifouling and anticorrosion performance of the antifouling and anticorrosion coating will be affected. This is because the catechol group in dopamine acrylamide can be used as a biomimetic anchor to produce a strong adsorption effect with the substrate through hydrogen bonding. The excellent adhesion ensures the long-term stability of the antifouling and anticorrosion coating in practical applications. During the long-term antifouling and anticorrosion process, the performance of the coating can still be maintained. However, the excess dopamine acrylamide in the antifouling and anticorrosion coating does not react, thereby affecting the surface energy of the coating and reducing the coating's ability to repel fouling organisms.

[0126] It can be seen from the test data of Example 1, Example 8 and Example 9 that when the curing time is too short or too long, the adhesion and antifouling and anticorrosion performance of the antifouling and anticorrosion coating will be affected. This is because when the curing time is too short, the components in the antifouling and anticorrosion coating will not react completely, and the unreacted components are easy to fall off or adhere to the surface of the coating during the test, affecting the surface energy of the coating, thereby reducing the adhesion and antifouling and anticorrosion performance of the coating. After the reaction of the components in the antifouling and anticorrosion coating is completed, continuing to increase the curing time will cause a waste of resources and increase the preparation cost.

[0127] It can be seen from the test data of Example 1, Comparative Example 1, Comparative Example 2 and Comparative Example 3 that the adhesion and anti-fouling and anti-corrosion performance of the anti-fouling and anti-corrosion coating can be greatly improved by compounding the thiol-modified hexahedral polysilsesquioxane and N-(2,4,6-trichlorophenyl)maleimide. This is because the thiol-modified hexahedral polysilsesquioxane utilizes the advantages of the Si-O-Si inorganic core structure to improve the mechanical strength of the coating, so that the coating is more stable in practical applications and can maintain the integrity of the coating even in harsh environments, thereby improving the adhesion and anti-fouling and anti-corrosion performance of the anti-fouling and anti-corrosion coating.

[0128] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A highly adhesive organic silicon marine antifouling and anticorrosion coating, characterized in that: The organic silicon marine antifouling and anticorrosive coating is obtained by coating a composite coating material on the surface of a substrate and curing it with light; The composite coating material comprises dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane, N-(2,4,6-trichlorophenyl) maleimide, a photoinitiator and toluene.

2. The organic silicon marine antifouling and anticorrosion coating with high adhesion according to claim 1, characterized in that: The mass ratio of the dopamine acrylamide, the thiol-modified hexahedral polysilsesquioxane, the thiol polydimethylsiloxane, the N-(2,4,6-trichlorophenyl)maleimide and the photoinitiator is (0.5-5):(0.5-5):(10-50):(0.5-2):(1-10); The ratio of the total mass of the dopamine acrylamide, the thiol-modified hexahedral polysilsesquioxane, the thiol polydimethylsiloxane, the N-(2,4,6-trichlorophenyl)maleimide and the photoinitiator to the volume of the toluene is (0.0625-0.375) g:1 mL.

3. The organic silicon marine antifouling and anticorrosion coating with high adhesion according to claim 1, characterized in that: The photoinitiator includes benzoin ethers and / or benzophenones; The material of the substrate includes any one of iron, aluminum, copper or glass.

4. A method for preparing a highly adhesive organic silicon marine antifouling and anticorrosion coating according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Dopamine acrylamide, mercapto-modified hexahedral polysilsesquioxane, mercapto polydimethylsiloxane, N-(2,4,6-trichlorophenyl)maleimide and a photoinitiator are dissolved in toluene, mixed evenly to obtain a composite coating material, the composite coating material is evenly coated on the surface of a substrate, and the organic silicon marine antifouling and anticorrosion coating is obtained by ultraviolet curing.

5. The preparation method according to claim 4, characterized in that: The dopamine acrylamide is prepared by the following method: Dopamine hydrochloride, sodium borate, sodium carbonate and deionized water are mixed uniformly to obtain a precursor solution, methyl acrylic anhydride solution is added dropwise to the precursor solution, and a reaction solution is obtained after uniform mixing. Alkaline solution is added dropwise to the reaction solution to adjust the pH value thereof, the reaction solution is heated to cause a nucleophilic reaction, and after the reaction is completed, separation and purification are performed to obtain the dopamine acrylamide.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the dopamine hydrochloride, the sodium borate, the sodium carbonate, the deionized water and the methacrylic anhydride solution is (1-10):(5-20):(1-10):(100-150):(1-10); The methacrylic anhydride solution is composed of methacrylic anhydride and an organic solvent, wherein the organic solvent includes any one of tetrahydrofuran, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or N-methylpyrrolidone, or a combination of at least two thereof; The mass fraction of the methacrylic anhydride solution is 90-95wt%; The concentration of the alkali solution is 0.1 to 3.0 mol / L; Adding alkaline solution dropwise to the reaction solution to adjust the pH value thereof to 8-10; The heating temperature of the nucleophilic reaction of the reaction solution is 25 to 65°C; The heating time of the nucleophilic reaction of the reaction solution is 6 to 36 hours; The separation and purification process comprises: An acid solution is added dropwise to the reaction product obtained by the nucleophilic reaction to adjust the pH value thereof to 1-2, and then extraction is performed using ethyl acetate and / or n-hexane as an extractant.

7. The preparation method according to claim 4, characterized in that: The thiol-modified hexahedral polysilsesquioxane is prepared by the following method: (3-mercaptopropyl)trimethoxysilane and hydrochloric acid solution are added to methanol for condensation reaction. After the reaction is completed, the hexahedral polysilsesquioxane modified with mercapto group is obtained by separation and purification.

8. The preparation method according to claim 7, characterized in that: The mass fraction of the hydrochloric acid solution is 35-40wt%; The volume ratio of the (3-mercaptopropyl)trimethoxysilane, the hydrochloric acid solution and the methanol is (1-5):(1-10):(30-80); The temperature of the condensation reaction is 70 to 120°C; The condensation reaction time is 18 to 30 hours.

9. The preparation method according to claim 4, characterized in that: The ultraviolet light wavelength used in the ultraviolet light curing is 365nm; The power of the ultraviolet light source used in the ultraviolet curing is 1 to 5W; The UV light intensity used in the UV curing is 0.48-2.0 W / cm 2 ; The curing time of the ultraviolet light curing is 60 to 300 seconds.

10. Use of the organic silicon marine antifouling and anticorrosion coating with high adhesion according to any one of claims 1 to 3, characterized in that: The organic silicon marine antifouling and anticorrosion coating is used for antifouling and anticorrosion of ship hulls.

Citation Information

Patent Citations

  • Preparation method of long-term stable amphiphilic antifouling coating based on mussel bionics

    CN111440519A

  • Polymer coating coated silicon-based negative electrode material, preparation method and application

    CN115954457A

  • Protective layer and foldable device

    US20230416442A1

Cited By

  • Biodegradable plastic and preparation method thereof

    CN120248570A

  • Modified polyurethane marine antifouling paint based on metal pyridine structure and preparation method thereof

    CN120574518A